Effect of preoperative radiation on free flap outcomes for head and neck reconstruction: An updated systematic review and meta-analysis. Issue 2 (February 2022) - Miller, Henry; Bush, Kathryn; Delancy, Matthew; Leo, Nicholas De; Joshi, Hansa; Saracco, Benjamin; Adams, Amanda; Gaughan, John; Bonawitz, Steven
Summary: Background: There is an ongoing debate about whether neoadjuvant radiation therapy is associated with higher rates of postoperative complications after head and neck reconstruction. Herle et al. conducted a systematic review in 2014 of 24 studies, finding higher complication rates in irradiated fields. We sought to perform an exhaustive updated systematic review and meta-analysis. Methods: We conducted an updated systematic review of the literature, as outlined in our protocol, which was registered on PROSPERO. Databases included Medline, Embase, Cochrane Central, and Web of Science. There were no limits placed on the date range, place of publication, or origin. Exclusion criteria included patients less than 18 years of age, studies with less than 20 participants ( n < 20), case studies, skull base reconstructions, and local tissue rearrangements. The combined results of the studies and relative risks (RR) were calculated. Results: 53 studies were included for analysis, including 5, 086 free flaps in an irradiated field, and 9, 110 free flaps in a non-irradiated field. Of the 53 studies, 21 studies overlapped with those discussed in Herle et al.'s study, with a total of 32 additional studies. Neoadjuvant radiation was found to be a statistically significant risk factor for postoperative complications (RR 1.579, P < 0.001), total flap failure (RR, 1.565; P < 0.001), and fistula (RR, 1.810; P < 0.001). Our work reaffirmed the findings of the Herle et al. study. Conclusion: Preoperative radiation was associated with a statistically significant increase in the risk of total flap failure, fistula, and total complications but not partial flap failure. These high-morbidity complications must be taken into consideration when determining which patients should receive neoadjuvant radiation therapy.